Alpha B crystallin accumulation is a specific response to Ha-ras and v-mos oncogene expression in mouse NIH 3T3 fibroblasts. - Klemenz, R (1991)
The conditional expression of the v-mos and Ha-ras(EJ) oncogenes in NIH 3T3 cells leads to the accumulation of a 23-kDa protein (p23) (R. Klemenz, S. Hoffmann, R. Jaggi, and A.-K. Werenskiold, Oncogene 4:799-803, 1989). We purified p23 to homogeneity and determined part of the amino acid sequence. The obtained sequence is identical with that of the eye lens protein alpha B crystallin. Northern (RNA) blot and Western immunoblot experiments were performed to demonstrate that alpha B crystallin mRNA and protein do indeed accumulate as a consequence of v-mos and Ha-ras oncogene expression. Comparison of cDNA clones obtained from the mRNA of eye lenses and of oncogene-expressing fibroblasts revealed identity between them. The major transcription initiation site of the alpha B crystallin gene in our experimental system was shown by primer extension experiments to be identical with the one used in eye epithelial cells. In addition, we identified a second minor initiation site 49 nucleotides further upstream. Serum growth factors did not stimulate alpha B crystallin expression in growth-arrested cells.